Nakuru County Gender-Transformative Socio-Technical Innovation Bundles (GTSTIBs) scaling roadmap - Lutomia, Cosmas Kweyu; Nyamolo, Victor; Echessa, Lynnette; Moraa, Linnet; Ouya, Fredrick; Karanja, David; Arinaitwe, Warren; Ketema, Dessalegn; Nchanji, Eileen (2025)
This roadmap sets a countywide plan to scale Gender-Transformative Socio-Technical Innovation Bundles (GTSTIBs) in Nakuru, building on 2022–2024 pilots. It pairs technical practices (improved seed, intercropping, mechanisation) with social innovations (gender dialogues, nutrition training, farmer-to-farmer learning) to lift productivity, equity and nutrition. Five pillars guide delivery: integrated pluralistic extension, alignment with CIDP via the CASSCOM gateway, private-sector partnership and finance, equity for women, youth and PWDs, and robust M&E for institutionalization. A five-year phased approach moves from foundation to expansion to full county ownership. Resourcing blends county/national budgets, development partners, private co-investment and farmer contributions, with risk mitigation and immediate next steps.